Concentration and compositional controls on degradation of permafrost‐derived dissolved organic matter on the Qinghai–Tibetan Plateau - Yinghui Wang; Yasong Wang; Lulu Han; Amy M. McKenna; Anne M. Kellerman; Robert G. M. Spencer; Yuanhe Yang; Yunping Xu (Limnology and Oceanography Letters, 2024)
Abstract Understanding the fate of permafrost‐derived dissolved organic matter (DOM) is critical for unraveling its role in carbon cycling. However, it remains unclear whether the high lability of permafrost‐derived DOM can be attributed to intrinsic chemical properties or elevated carbon concentrations. We investigated the dynamics of permafrost DOM from the Qinghai–Tibetan Plateau using both biodegradation and photodegradation experiments. Biodegradation and photodegradation of permafrost‐derived DOM exhibited distinct qualitative preferences for specific chemical groups (i.e., peptide‐like and aromatics, respectively). Notably, reducing the initial concentration of dissolved organic carbon (DOC) by half and a quarter resulted in shifts in biodegradable DOC content from 11.2% to 11.5% and 8.5%, respectively, accompanied by a corresponding decrease in the biodegradation rate from 0.11 to 0.06 and 0.03. This insight highlights the importance of recognizing the interplay between DOM quality and concentration and bears broader significance for our understanding of the fate of permafrost‐derived DOM in natural ecosystems.